Sobre algumas das transformações do conceito de narcisismo no modelo psicanalítico freudiano - Campos, Erlon de Araújo (2011)
The focus of this work is basically the evolution of the concept of narcissism in Freud's psychoanalytical model. Thus it seeks to grasp Freud s meaning of this notion from the initial propositions registered in his work. It is possible to observe explanations to certain types of choice of object as a result of fixation and identification mechanisms, which lead to a choice whose object resembles the very ego of the subject involved in such a process. This work also points to the characterization of narcissism when Freud understood it as a developmental stage between autoeroticism and love for object. However, this research will deal in some detail with which is considered the deepest and most comprehensive point about narcissism in Freud s work: the text Introduction to narcissism. For this approach a key premise will be the inextricable relation between the notion of narcissism and the idea of instinct and, as a consequence, the resulting changes of the instinct dynamics with Introduction to narcissism, specifically the investments of libido, which as from this moment is described as investing not only in external objects but also in ego itself. Also based on the same texts, the anaclitic and narcissistic choices of objects are considered, as well as the notion of primary and secondary narcissism and the ideas of ideal ego and ego s ideal. Finally, this research seeks to identify the existence of more significant changes in narcissism by the time Freud introduced the second topography. In that direction, it can be noticed some noticeable changes related to primary narcissism, presented at this theorization phase as a more primal and unobjectal stage in comparison with Freud s first suggestions, and to secondary narcissism, which at this moment corresponds to the first concept of primary narcissism